Supplementation of Multiple Enzymes and Organic Trace Mineral Supplementation to the Diets Containing Sub-Optimal Energy on Performance and Carcass Traits of Commercial Broilers - Krishna, Daida; Gurram, Srinivas (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the performance and carcass parameters of broilers fed with sub-optimal metabolizable energy (100 and 200 kcal/kg less ME) diets supplemented with multiple Enzyme (400g/ton feed) and organic trace mineral supplement. A total of 300-day-old commercial broiler chickens were distributed in a completely randomized design into 6 treatments with 10 replicates of 5 chicks each. Treatments comprised of T1- basal diet (BD) without enzyme (EZ) or organic mineral (OM) supplementation; T2- 100 kcal/kg less metabolizable energy (ME) without EZ and OM (BD 1); Â T3- 100 kcal/kg less ME with EN (BD1+EZ); T4- 200 kcal/kg less ME without EN and OM (BD 2); T5- 200 kcal/kg less ME with EZ (BD2+EZ); T6- BD with organomin supplementation (BD+OM).The results revealed significantly (P